Material Meaning: Narcissists Gain Existential Benefits From Extrinsic Goals. (March 2017) - Abeyta, Andrew A.; Routledge, Clay; Sedikides, Constantine
The present research examined how narcissism is related to perceptions of meaning derived from distinct types of life goals, namely, extrinsic and intrinsic. Although in most cases extrinsic goals are inversely associated with well-being, we propose that narcissists' pursuit of extrinsic goals (e.g., wealth, fame) is positively linked to meaning in life. In Study 1, higher levels of narcissism corresponded with viewing extrinsic goals as more meaningful. In Study 2, focusing participants on the extrinsic, relative to intrinsic, value of their goal pursuit increased meaning among narcissists. Taken together, narcissists derive meaning from extrinsic goals.